2015
DOI: 10.1037/a0037758
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: Teachers’ influence during peer collaboration.

Abstract: This study examined the influence of teachers' instructional moves on students' relational thinking during small-group collaborative discussions. One hundred and twenty 4th grade students and 6 teachers participated in a series of 10 discussions, generating a video-recorded corpus containing 32,511 turns for speaking. A microanalysis of a subset of the corpus showed that teacher prompts for relational thinking, rather than lower level prompts or prompts for evaluation, had an immediate effect on student relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Whether students are able to apply and integrate information provided by their teacher into their ongoing work appears to be crucial for student learning Webb & Farivar, 1999). Previous studies have shown a positive relationship between students' uptake of teachers' instructional moves and student learning (Jadallah et al, 2011;Lin et al, 2015). When applying support, students often mirror teachers' behavior or helping style (Gillies, 2011;Jadallah et al, 2011;.…”
Section: Teacher Support Uptake and Student Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether students are able to apply and integrate information provided by their teacher into their ongoing work appears to be crucial for student learning Webb & Farivar, 1999). Previous studies have shown a positive relationship between students' uptake of teachers' instructional moves and student learning (Jadallah et al, 2011;Lin et al, 2015). When applying support, students often mirror teachers' behavior or helping style (Gillies, 2011;Jadallah et al, 2011;.…”
Section: Teacher Support Uptake and Student Learningmentioning
confidence: 99%
“…Such mirroring is assumed to catalyze the students' interaction. For example, Lin et al (2015) wrote, "Once a teacher stimulates one student to generate relational thinking, other students in the group spontaneously generate relational thinking collaboratively at an accelerating rate without further teacher support" (p. 625). However, to our knowledge, no study has investigated students' delayed uptake of the content of a teacher's support (e.g., an explanation of the meaning of a particular concept) after the teacher has left a group of students and how this affects students' learning.…”
Section: Teacher Support Uptake and Student Learningmentioning
confidence: 99%
“…For example, to promote increased use of evidence in arguments, fourth grade teachers used such scaffolding means as praise and prompting for evidence, which led to enhanced use of evidence by the students . To promote the consideration of the relations between different entities involved in a problem, teachers can prompt students to consider such relations and illustrate how to do so; this led elementary students to successfully consider such relations (Lin et al, 2014). In another example, teachers can use questioning and other strategies to help struggling first grade students learn to read; this helped such students rapidly reach grade-level reading proficiency (Rodgers, 2004).…”
Section: One-to-one Scaffoldingmentioning
confidence: 99%
“…The third component, teacher modeling and scaffolding, refers to a set of teacher discourse moves (e.g., prompting, marking, or summarizing) that can be used to guide students toward productive talk (Van de Pol et al, 2010;. Indeed, the use of specific teacher discourse moves may contribute to the generation of desirable student discourse (Lin et al, 2015). For instance, the teacher may use modeling to raise an authentic question or use promoting to provoke thinking and linking with the text.…”
Section: Qt Modelmentioning
confidence: 99%